Investigation of the effective transmittance of Mach-Zehnder interferometer in the multi-longitudinal-mode high-spectral-resolution lidar. (January 2023) - Gao, Fei; Gao, Fengjia; Yang, Xiao; Li, Gaipan; Wang, Li; Wang, Meng; Hua, Dengxin; Močnik, Griša; Stanič, Samo
Highlights: Effective transmittance of MZI is a key parameter in the retrieval of aerosol characteristics using the MLM HSRL technique. Effective transmittance of MZI is investigated using theoretical analysis, optical simulation and experimental measurement. Retrieval uncertainty of aerosol backscattering coefficient is estimated using the complex degree of coherence of MZI. Abstract: Effective transmittance is an important parameter of Mach-Zehnder interferometer in the retrieval of aerosol optical properties using the multi-longitudinal-mode high-spectral-resolution lidar, which is a function of the complex degree of coherence. In this paper, we retrieve the parameter of the complex degree of coherence for the multi-longitudinal-mode laser from the theoretical analysis, optical simulation and experimental measurements, which are 0.726, 0.678 and 0.453 using the Mach-Zehnder interferometer with the optimal optical path difference of two times of laser optical cavity length (∼1000 mm) and under the light illumination of the high power Nd:YAG laser with the mode number of 101 and mode interval of 300 MHz under the condition of laser linewidth of 1 cm −1 (30 GHz). The preliminary measurement results of aerosol optical properties using the constructing multi-longitudinal-mode high-spectral-resolution lidar show that the difference of the complex degree of coherence retrieved from the presented methods results in the relative error of 40% in the aerosol backscattering coefficient with thin cloud layer and 90% with the presence of dense aerosol layer.